Dual CSF1R inhibition and CD40 activation demonstrates anti-tumor activity in a 3D macrophage- HER2+ breast cancer spheroid model - Rodriguez-Perdigon, Manuel; Haeni, Laetitia; Rothen-Rutishauser, Barbara; Rüegg, Curzio (Frontiers in Bioengineering and Biotechnology, 2023)
The complex interaction between tumor-associated macrophages (TAMs) and tumor cells through soluble factors provides essential cues for breast cancer progression. TAMs-targeted therapies have shown promising clinical therapeutical potential against cancer progression. The molecular mechanisms underlying the response to TAMs-targeted therapies depends on complex dynamics of immune cross-talk and its understanding is still incomplete. In vitro models are helpful to decipher complex responses to combined immunotherapies. In this study, we established and characterized a 3D human macrophage-ER+PR+HER2+ breast cancer model, referred to as macrophage-tumor spheroid (MTS). Macrophages integrated within the MTS had a mixed M2/M1 phenotype, abrogated the anti-proliferative effect of trastuzumab on tumor cells, and responded to IFN with increased M1-like polarization. The targeted treatment of MTS with a combined CSF1R kinase inhibitor and an activating anti-CD40 antibody increased M2 over M1 phenotype (CD163+/CD86+ and CD206+/CD86+ ratio) in time, abrogated G2/M cell cycle phase transition of cancer cells, promoted the secretion of TNF-α and reduced cancer cell viability. In comparison, combined treatment in a 2D macrophage-cancer cell co-culture model reduced M2 over M1 phenotype and decreased cancer cell viability. Our work shows that this MTS model is responsive to TAMs-targeted therapies, and may be used to study the response of ER+PR+HER2+ breast cancer lines to novel TAM-targeting therapies.